Aspects of inflammation in asthma - Kalla, Ismail Sikander (My University, 2017)
Asthma is the most prevalent chronic respiratory disease worldwide, with South Africa having the fourth highest asthma mortality rate in the world (1.5 per 100,000 people) and the fifth highest asthma mortality among five to thirty-five year old asthmatics (18.5 per 100,000 asthmatics). Current guidelines recommend that the achievement of ‘asthma control’ may still be plagued with persistent airway inflammation despite normalisation of spirometric parameters and control of asthmatic symptoms. This may result in structural damage with airway remodelling, fibrosis and progressive loss of lung capacity over time. Assessment of inflammation,‘Inflammometry’ is now increasingly used to titrate therapeutic interventions and achieve better asthma control. The current study aims to identify simple, objective, non invasive and reproducible biomarkers for airway inflammation; that would allow documentation of the presence or absence of airway inflammation in individual asthmatic patients. The availability of such tests may allow titration of therapeutic interventions to an outcome parameter that is a true reflection of the state of inflammation of the airways. This was a prospective, single centre, cross-sectional study of patients with confirmed asthma attending a dedicated specialist asthma clinic at the Charlotte Maxeke Johannesburg Academic Hospital Asthma Clinic. Patients attending the clinic were identified from patient records and those who met the inclusion and exclusion criteria, were selected for the study. The level of asthma control of each patient was determined using the Asthma Control Questionnaire (ACQ). Patients undertook the Asthma Control Test (ACT), had an independent assessment of their asthma control as well as performed lung function tests in a dedicated lung function laboratory. Blood and exhaled breath samples from patients were analysed for inflammatory biomarkers. Optimisation experiments were performed to establish a protocol for the measurement of serum leukotrienes in the asthmatic patient. For the statistical analyses, patients were characterised into asthma control groups as defined by the ACQ. The current study found that the ACQ and the ACT, as well as the ACQ and an independent physician’s assessment of the level of asthma control were in synchrony. Baseline FEF 25-75 levels, expressed as percentage of predicted, were low in the totally controlled, well-controlled and uncontrolled groups of asthmatic patients with medians of 35.7%, 27.3% and 17.3% respectively. The FEF 25-75 values in the three groups demonstrated an absolute post bronchodilator reversibility of 32%, 27% and 31% respectively. These findings confirmed the presence of bronchial airway hyper-reactivity (BAH), and suggest probable remodelling in the small airways. Impulse oscillometry (IOS) had a greater value in differentiating small airway resistance in the controlled when compared to the uncontrolled adult asthmatic patient. Biomarker assessments found that CRP, IL-2 and RANTES were significantly higher in the uncontrolled group when compared with the controlled group of asthmatic patients (p = 0.03, p = 0.02 and p = 0.03 respectively). Of the three serum leukotrienes measured (i.e. LTB4, LTC4 and LTE4), LTE4 levels were significantly higher in the totally controlled group compared to the uncontrolled and well-controlled groups (p = 0.007 and p = 0.006 respectively). Therefore, an elevated LTE4 coupled to a suppressed level of RANTES in the same patient may identify a different asthma phenotype. This could provide opportunities for identifying asthma phenotypes and using biomarkers in assessing asthma control. The study also found that TGFβ1 and TGFβ2 levels were significantly higher in patients using high-dose inhaled corticosteroids (ICS) (dose category as defined by the Global Initiative for Asthma (GINA)), compared to those patients not using high-dose ICS (p = 0.01 and p = 0.001 respectively). By comparison, TGFβ1 and TGFβ2 levels were significantly lower in the patients using moderate-dose ICS (dose category as defined by GINA), compared to those not using moderate-doses of ICS (p = 0.02 and p = 0.001 respectively). These findings suggest that airway inflammation is modulated by the upregulation of Treg cells as TGFβ is produced by Treg cells. It is also possible that Treg cells under the influence of elevated IL-2 levels inhibited the expression of the other Th1 as well as Th2 cytokines measured. Therefore, an elevated TGFβ level coupled with an elevated IL-2 level in the same patient may also identify a different asthma phenotype. Collectively, biomarker assessments may prove useful in assessing asthma control. Such assessments may require individualisation for different asthma endotypes and phenotypes, possibly even using biomarker profiling using multiple biomarkers for future patient care considering the heterogeneity of inflammation in asthma.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD), 2017
Keywords: Inflammation; Inflammation--therapy